Adsorptive Removal of Congo Red by PVDF/MIL⁃53(Fe) Composite Membrane from Aqueous Solution - Hai XING; Xiaohua WANG; Ningning LIU (Liaoning Shiyou Huagong Daxue xuebao)
Metal⁃organic framework material MIL⁃53(Fe) was added as a modifier to polyvinylidene fluoride (PVDF) casting solution, and PVDF/MIL⁃53(Fe) composite membrane was fabricated. The composite membranes were characterized by a series of tests, including XRD, FT⁃IR, SEM and TG. The composite membrane was used as an adsorbent to adsorb Congo red (CR) from aqueous solution. The effects of composite membrane dosage, initial concentration of CR solution, contact time and temperature were discussed, and the isothermal adsorption models, adsorption kinetics, and adsorption thermodynamics were also studied. The results show that the most appropriate dosage of the composite membrane is 20 mg in each experiment. The maximum theoretical adsorption capacity of CR by the composite membrane is 71.9 mg/g at 313 K. Ethanol has good desorption effect on CR adsorbed onto the composite membrane, and the composite membrane can maintain good adsorption capacity after 5 adsorption⁃desorption cycles. The isotherm data follows the Langmuir isotherm model and the kinetic adsorption follows the pseudo⁃second⁃order model. This adsorption process is spontaneous and endothermic, which is illustrated by the thermodynamic data.